2014
DOI: 10.1128/iai.01461-13
|View full text |Cite
|
Sign up to set email alerts
|

Janus Kinase 3 Activity Is Necessary for Phosphorylation of Cytosolic Phospholipase A2 and Prostaglandin E2 Synthesis by Macrophages Infected with Francisella tularensis Live Vaccine Strain

Abstract: Francisella tularensis, the causative agent of tularemia, modulates the host immune response to gain a survival advantage within the host. One mechanism of immune evasion is the ability of F. tularensis to induce the synthesis of the small lipid mediator prostaglandin E2 (PGE 2 ), which alters the host T cell response making the host more susceptible to Francisella growth. PGE 2 is synthesized by a tightly regulated biosynthetic pathway following stimulation. The synthesis of PGE 2 begins with the liberation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…JAK3 has been shown to phosphorylate insulin receptor substrate-1 (IRS-1), IRS-2, PI3K/Akt and focal adhesion kinase (FAK) [38], which contain SH2 or other phospho-tyrosine-binding domains. Other studies have used Drosophila to investigate the JAK/STAT pathway in ovarian cell migration, sex determination and stem-cell maintenance [39, 40], and in macrophages infected with F. tularensis, JAK3 is involved in the phosphorylation of p38MAPK [41]. Herein, we observed that JAK3 strongest expression was found in the dominant follicle, which is active and growing while in the ovulatory follicle, following the endogenous LH surge or hCG injection, JAK3 expression was dramatically reduced.…”
Section: Discussionmentioning
confidence: 99%
“…JAK3 has been shown to phosphorylate insulin receptor substrate-1 (IRS-1), IRS-2, PI3K/Akt and focal adhesion kinase (FAK) [38], which contain SH2 or other phospho-tyrosine-binding domains. Other studies have used Drosophila to investigate the JAK/STAT pathway in ovarian cell migration, sex determination and stem-cell maintenance [39, 40], and in macrophages infected with F. tularensis, JAK3 is involved in the phosphorylation of p38MAPK [41]. Herein, we observed that JAK3 strongest expression was found in the dominant follicle, which is active and growing while in the ovulatory follicle, following the endogenous LH surge or hCG injection, JAK3 expression was dramatically reduced.…”
Section: Discussionmentioning
confidence: 99%
“…PGH 2 is isomerized to PGE 2 by microsomal prostaglandin E synthase (mPGES1). We previously demonstrated that F. tularensis-induced PGE 2 synthesis by macrophages requires cPLA 2 , COX-2, and mPGES1 (8,18), yet we observed a temporal disconnect between cPLA 2 activation and the time at which increases in COX-2 protein and PGE 2 synthesis are observed. AA release and utilization by COX-2 are highly coupled events, and this apparent disconnect between cPLA 2 activation and the increase in COX-2 protein led us to hypothesize that an alternative pathway utilizing other phospholipases was required for supplying AA to the inducible PGE 2 biosynthetic pathway in F. tularensis-infected macrophages.…”
mentioning
confidence: 63%
“…We have previously demonstrated the requirement of cPLA 2 for F. tularensis LVS-induced PGE 2 synthesis; however, the observed temporal disconnect between cPLA 2 activation and detectable PGE 2 synthesis suggested that cPLA 2 was not supplying AA that was being converted into PGE 2 in these infected macrophages (18). Our results demonstrating that cPLA 2 inhibition only partially blocks late AA release or that the addition of exogenous AA does not restore PGE 2 biosynthesis by cPLA 2 -inhibited infected macrophages would support this model.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations